Effect of gamma radiation on lipids by the TBARS and NMR - Adriana Cristina de Oliveira Silva; Eliane Teixeira Mársico; Edgar Francisco Oliveira de Jesus; Carlos Frederico Guimarães; Marco Antonio Sloboda Cortez (Brazilian Archives of Biology and Technology, 2011)
The aim of this work was to study the effect of gamma radiation on lipids by TBARS and NMR. The samples of raw whole milk were subjected to gamma radiation from Co60 in doses of 1, 2 and 3 kGy and the production of rancidity was studied through Nuclear Magnetic Resonance (NMR) and Thiobarbituric Acid Test (2-TBARS). The TBARS values increased according to the intensity of the radiation dose applied at the samples, demonstrating correlation between the radiation dose and the production of lipid oxidation. This was confirmed by NMR with the formation of peaks of aldehydes and ketones that were small and similar in the doses of 1 and 2 kGy. In the dose of 3 kGy, the total degradation of milk fat was observed. A correlation between the NMR and 2-TBA was detected.